Practical aspects of ozone therapy: Checking the generated ozone concentration / average lifetime of gas in the syringe (Ozone Therapy Global Journal, 2013)
Despite the current advances in the medical uses of ozone, some aspects of theclinical handling of this gas have not been clarified and studied property. The presentwork applies a spectrophotometric method for controlling the concentration of themedical ozone generator. In addition we studied the half life time of the ozone insidea syringe located at different positions. As was demonstrated by performingspectrophotometric measurement (240nm) and by mathematical calculations (takinginto account working temperature and pressure) is possible to know the concentrationof ozone generated by ozone devices for clinical use. This method is useful in case ofdoubt about the right functioning of the device or if it suspected a loss of calibration.Additionally, it was demonstrate the importance of using O3 in the first 10 min afterbeing generated, because the loses of the10% of the initial dose. Also it was foundthat the position, in which the syringe is placed, even if advised to have it with the coneup, is not decisive in handling the gas.